Everyday citizenship: people, place and politics in Philippi - Maurtin, Leigh (School of Architecture, Planning and Geomatics, 2023)
In the South African context, political and universal rights of citizens have been expanded since liberation but the basic services and livelihoods have eroded (Miraftab, 2009). Marginalized citizens have created their homes through auto construction, and self-making, in the post-apartheid city (Caldeira, 2017). This is evident in spaces like Philippi, where areas of Neoliberal planning practices remain as exclusionary imaginaries of city and citizenship that promote collective amnesia (Miraftab, 2009). Insurgent planning scholarship calls for collective memory and looks to liberating planning imaginaries and histories of marginalized people as strength in knowledge (Miraftab, 2009). Through ways of being and social spatial production practices, people are infrastructure (Simone, 2004). The social practices and community agencies inform a type of infrastructure. Amin (2014) speaks of the liveliness of infrastructure. The term infrastructure is used loosely. It indicates the bigger infrastructural elements like transport infrastructure, yet to come in Philippi, as well as other more basic infrastructure like water, sanitation, and electricity, which are often void in spaces in Philippi. Amin (2014) highlights the politics of community and institution, and visible and invisible infrastructure (Amin, 2014). Networks of social gathering spaces, such as economic trade and eating areas, and physical space, like places of water collection and sanitation, give a rendering of the urban poor experience. As part of the experience of these infrastructures, the sensory landscape of urban places holds collective memory and social outlook (Amin, 2014). Acknowledging and paying homage to this helps an understanding of the noteworthy social, cultural and spatial rituals of place and self-built placemaking in Philippi. Through investigating planned and self-built places and their everyday practices, this study has attempted to collect spatial practices, to inform a framework that considers this narrative and the interventions it suggests. The collection of information has been used to guide and inform design principles for interventions at various scales. The starting point of the inquiry is the pavement. A universal everyday place that all actors engage with. In Philippi, the pavement and walkways offer many everyday practices. The pavement is the most common public space of movement, social exchange, and public and private interface, and the investigation of the street in Philippi has informed other areas of design intervention.